The Influence of Emotional Experience on the Success of Viral Marketing Strategies in the Food and Beverage Industry - Bunjamin*, Thalia Sharon; Aprilian, Elvin Eka; Ananda, Artha Sejati; Polla, Johanes Ronaldy (Universitas Syiah Kuala, 2024)
This research explores the impact of emotional experiences on the effectiveness of Viral Marketing strategies within the Food and Beverage (FnB) industry. The study examines the correlation between emotional content in social media and its ability to engage consumers, ultimately contributing to the success of viral marketing campaigns. The research utilizes a sample collected over a brief period, focusing on emotional factors and the relevance of content to consumer sharing behavior. Academic recommendations emphasize the need for future studies to employ larger samples and more specific variables to enhance the depth and accuracy of results in understanding Viral Marketing strategies. Practical recommendations suggest that businesses in the FnB industry should consider incorporating specific emotional elements into their social media content, alongside ensuring relevance to current trends and public interests. The findings indicate that emotionally resonant and relevant content holds the potential to captivate consumers, fostering increased interaction and content sharing.